Intestinal methane production is associated with decreased weight loss following bariatric surgery. Issue 6 (November 2016) - Mathur, Ruchi; Mundi, Manpreet S.; Chua, Kathleen S.; Lorentz, Paul A.; Barlow, Gillian M.; Lin, Eugenia; Burch, Miguel; Youdim, Adrienne; Pimentel, Mark
Summary: To determine whether methane and hydrogen on breath test affects weight loss after bariatric surgery, 156 subjects (pre-surgery BMI ≥33) were recruited ≥4 months after surgery. Pre- and post-surgery weights and BMIs were recorded. Post-surgery methane and hydrogen levels were determined. % total weight loss and % change in BMI were prorated to six months after surgery. M+/H+ subjects ( N  = 13) exhibited lower prorated % change in BMI vs. all other subjects ( N  = 144) ( p  = 0.13), and significantly lower prorated % total weight loss ( p  = 0.036). These findings may suggest that subjects with positive breath methane and hydrogen lose less weight following bariatric surgery.